PRR enhances anti-tumor immunity and suppresses colitis by promoting the development and survival of naive T and iNKT cells - Shimba, Akihiro; Munakata, Satoru; Abe, Shinya; Cui, Guangwei; Kato, Ryoma; Miyazaki, Masaki; Ichihara, Atsuhiro; Ikuta, Koichi (Frontiers in Immunology, 2025)
The (pro)renin receptor (PRR) is a multifunctional transmembrane protein that enhances β-catenin/TCF1 signaling and V-ATPase-mediated lysosomal acidification. Emerging evidence indicates that it may also regulate potential roles in regulating T cell development, survival, and immune responses. Here, we demonstrated that PRR promotes the maturation and survival of T cells within the thymus. In particular, PRR-deficient mice exhibited a significant reduction in iNKT cells in the thymus and periphery. PRR promoted the energy synthesis process in mitochondria, as evidenced by increased mitochondrial amount and membrane potential. This phenomenon was accompanied by an increase in TCF1 expression and lysosomal acidification. Furthermore, PRR enhanced the survival of naive T and iNKT cells in the periphery, while simultaneously suppressing inflammatory cytokine-producing T cells, thereby preventing colitis. In contrast, PRR enhanced resistance against tumor growth by increasing the number of tumor-infiltrating Th1 and iNKT cells, which in turn promoted NK cell recruitment. This study indicates that PRR is critical for supporting T cell maintenance, suppressing excessive inflammation, and enhancing anti-tumor immunity.